Macrocomplexes and discordant high-sensitivity cardiac troponin concentrations. (July 2018) - Kavsak, Peter A; Roy, Chantele; Malinowski, Paul; Mark, Ching-Tong; Scott, Terry; Clark, Lorna; Lamers, Shana; Ainsworth, Craig
Background: Analytical comparisons between different high-sensitivity cardiac troponin (hs-cTn) assays are important for reassurance of results performed with different methodologies and to identify potential interferences or confounders to result interpretation. Our objective in the present study was to compare Beckman Coulter's latest hs-cTnI assay to Abbott's hs-cTnI assay and to assess agreement between results. Methods: Two hundred ethylenediaminetetraacetic acid plasma samples that had clinically reported hs-cTnI results from the Abbott ARCHITECTi2000 that spanned the analytical range were stored (median = 4 h), re-centrifuged and retested for hs-cTnI on the Abbott ARCHITECTi1000 and Beckman Coulter Access2 analysers. Passing–Bablok regression and fold-differences were evaluated, with differences approximately three-fold between results further subjected to Roche hs-cTnT testing and polyethylene glycol precipitation. Results: The Beckman and Abbott hs-cTnI concentrations were correlated ( r  = 0.95) with Beckman yielding proportionally lower concentrations (slope = 0.78; 95%CI: 0.74–0.85). There were 12 samples that yielded Abbott hs-TnI concentrations ≥3-fold higher than the Beckman hs-cTnI concentrations; of which nine samples from seven different patients had sufficient quantity for additional testing. All seven patients had macrocomplexes as determined with polyethylene glycol precipitation that affected the Abbott hs-cTnI assay. One patient with Abbott hs-cTnI results >1300 ng/L had polyethylene glycol, heterophile antibodies and creatine kinase-MB testing performed which confirmed that a macrocomplex most likely affected the Abbott and Roche (hs-cTnT = 65 ng/L) assays but not the Beckman (hs-cTnI = 12 ng/L) assay. Conclusion: The hs-cTnI concentrations obtained from ethylenediaminetetraacetic acid plasma between the Beckman and Abbott assays are highly correlated, with large differences in concentrations (≥3-fold) between Abbott and Beckman assays possible due to macrocomplexes.